2022
DOI: 10.3390/ijerph192316243
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice in a Sample of the Lebanese Population Regarding Cholera

Abstract: The evaluation of knowledge, attitude, and practices towards an emerging disease is an essential component of public health preventive measures during an outbreak. In October 2022, an outbreak of cholera was reported in Lebanon, which is the first to be reported in the Middle Eastern country for 30 years. This study aimed to explore the level of knowledge as well as attitude and practice of the general public in Lebanon towards cholera. A self-administered structured questionnaire was distributed via an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Compared to previous studies, a study revealed that 35.2% of health workers had good knowledge of cholera [ 30 ]. In Lebanon, 32.5% of the general population had good knowledge about cholera [ 20 ]. The low level of knowledge among medical students could be explained by regional variations in prevalence, as cholera is somehow limited to poor areas with limited access to clean water.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous studies, a study revealed that 35.2% of health workers had good knowledge of cholera [ 30 ]. In Lebanon, 32.5% of the general population had good knowledge about cholera [ 20 ]. The low level of knowledge among medical students could be explained by regional variations in prevalence, as cholera is somehow limited to poor areas with limited access to clean water.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected using a selfadministered questionnaire distributed online using a snowball sampling approach starting with the contacts of the authors in Jordan. The survey structure was based on a previous KAP survey which was conducted in Lebanon by the end of 2022 by Malaeb et al [52]. Additionally, the assessment of psychological determinants of attitude towards cholera vaccination was based on four items adopted from the 5C scale and its validated version in Arabic [27,28,53].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study from 2021 among the general public in Jazan, Saudi Arabi showed poor level of cholera knowledge manifested in less than 44% who knew that the causative agent is a bacterium [45]. A higher level of knowledge regarding cholera transmission, treatment, and prevention was reported by Malaeb et al in a sample of 553 participants surveyed in late 2022 amid the outbreak in Lebanon [52]. An earlier study that was conducted in 2017 in the Yemeni Southern city of Aden identi ed poor level of knowledge regarding cholera transmission and prevention [60].…”
Section: Attitude To Cholera Vaccinationmentioning
confidence: 96%
See 1 more Smart Citation
“… 42 , 43 In early October 2022, there was a rapid spread of cholera caused by Serotype O1 El‐Tor Ogawa in Syria and Lebanon. 44 , 45…”
Section: Cholera Serologymentioning
confidence: 99%